PERAN POLA ASUH ORANG TUA DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS III SEKOLAH DASAR NEGERI 158 GRESIK - Arvanzha Putra Soenartok; Nafiah; Pance Mariati; Sri Hartatik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the role of parenting patterns to help shape a child's character and interest in learning. Some children have bad behavior in learning, lack of interest in learning, lack of learning support to achieve achievements. Sometimes the child needs to be given a good example so that he can be a good example, the child also needs support or appreciation to achieve achievements and how a parent's efforts to prevent and solve the problem of low interest in learning. The purpose of this study was to describe the factors of low interest in learning in students at SDN 158 grade 3 Gresik Regency and to describe the role of parenting patterns to increase interest in learning students at SDN 158 grade 3 Gresik Regency and to describe the obstacles for parents to carry out parenting patterns to increase interest in learning at SDN 158 grade 3 Gresik Regency. The type of research used is a descriptive qualitative approach. This study uses data collection techniques with Observation, Interviews, and Documentation. The data analysis techniques used are data condensation, data presentation and drawing conclusions. The data validity test used in this study is time triangulation. The results of the study of the role of parenting patterns in increasing interest in learning in grade III students at SDN 158 Gresik. The factors for low interest in learning are many and varied, including: 1) internal factors including children are not interested in learning because they tend to prefer watching television, children are not interested in learning because they tend to prefer playing with cellphones, children are not interested in subjects, lack of discipline from parents for children and lack of motivation to learn from parents to increase children's interest in learning. 2) external factors that include a bad environment that makes children influenced by bad things, giving freedom to children without any limits so that children are more interested in playing than studying, not providing discipline to children so that children always break the rules, lack of parental attention to provide learning motivation so that children have no interest in learning. The efforts of parents in increasing interest in learning are by: 1) providing opportunities to play but with limits, 2) providing rules for children to be disciplined, 3) providing learning motivation to children so that they have an interest in learning.